Correlation between Nafion Morphology in Various Dispersion Liquids and Properties of the Cast Membranes - Ekaterina Yu. Safronova; Daria Yu. Voropaeva; Dmitry V. Safronov; Nastasia Stretton; Anna V. Parshina; Andrey B. Yaroslavtsev (Membranes, 2022)
Nafion is a perfluorosulfonic acid polymer that is most commonly used in proton-exchange membrane fuel cells. The processes of pretreatment and formation of such membranes strongly affect their properties. In this work, dispersions of Nafion in various ionic forms and dispersing liquids (ethylene glycol, N,N-dimethylformamide, N-methyl-2-pyrrolidone and isopropyl alcohol–water mixtures in different ratios) were obtained and studied. Membranes fabricated by casting of the various dispersions were also studied. The effect of the nature of the dispersing liquid and the counterion on the properties of Nafion dispersions, the morphology of the polymer in the dispersions and the characteristics of the membranes obtained from them has been shown. Based on the overall results, it can be concluded that the use of perfluorosulfonic acid dispersions in aprotic polar solvents is advisable for obtaining membranes by the casting procedure. This is because it provides optimal polymer morphology in the dispersion, which leads to the formation of films with good selectivity, mechanical and transport properties. The performed investigations show the relationship between the composition of dispersions, the morphology of the polymer and the properties of the membranes formed from them by the casting procedure.